The social construction of educational technology through the use of authentic software tools - Allan Jones; Christopher Bissell (Association for Learning Technology, 2011)
A major strand of science and technology studies in recent decades has relatedto the social construction of technology (SCOT) movement, whose adherentsmaintain that technological systems are determined just as much by social forcesas by technological ones. Taking this SCOT notion as a starting point, and puttinga focus on the user, this paper looks at some examples of the educationaluse of software tools that exploit the functionality of the software in ways farremoved from the original design. Examples include the use of spreadsheets,graphics editors and audio editors, and online translation software. Connectionsare made between the social construction of technology and constructivist pedagogy,particularly in relation to authentic learning.